강화해협이 홍수 및 조석에 대하여 한강하류부에 미치는 영향 연구 - 박효선; 최계운; 변성준 (한국수처리학회지, 19(4), 2011)
The Ganghwa Strait is located in Han river estuary, where the Han river, Imjin river and Yeseong river meet. And the velocity is so fast in the narrow strait. Moreover, a great deal of flow discharge into the Gyeonggi bay by the periodically repeated tides. A great deal of river sediment that inflow from the upstream of Han river can be accumulated there or discharged into the adjoining shore. In this study, the variation of flow characteristics is analyzed in the Han river and Imjin river located in the Han river estuary, with and without the consideration of the Ganghwa Strait's existence. The analysis of steady flow and unsteady flow was made utilizing the MIKE 11 Model. The simulation result shows that the maximum water level rose 8.21% when the design rainfall is increased during the flood period simulation with the closure of Ganghwa strait. And in the state of steady flow analysis, the maximum change rate is 8.25% when the designed flood was simulated with a return period of 200-year. KCI Citation Count: 1